Simulation Design of Artificial Intelligence Controlled Goods Transport Robot - Oktarina, Yurni; Sastiani, Destri Zumar; Dewi, Tresna; Kusumanto, RD (Computer Engineering and Applications Journal (ComEngApp), 2022)
Technological advances enable scientists and researchers to develop more automated systems for life's convenience. Transportation is among those conveniences needed in daily activities, including warehouses. The easy-to-build and straightforward transport robot are desired to ease human workers' working conditions. The application of artificial intelligence (AI), Fuzzy Logic Controller, and Neural Network ensures the robot is able to finish assigned tasks better and faster. This paper shows the concept design of an AI-controlled good transport robot applied in the warehouse. The design is made as fast and straightforward forward possible, and the feasibility of the proposed method is proven by simulation in Scilab FLT and Neuroph.